Quasi $θ(τ_1,τ_2)$-continuity for Multifunctions (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of multifunctions called upper quasi $θ(τ_1,τ_2)$-continuousmultifunctions and lower quasi $θ(τ_1,τ_2)$-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper quasi $θ(τ_1,τ_2)$-continuous multifunctions and lower quasi $θ(τ_1,τ_2)$-continuous multifunctions are established.
Keywords: upper quasi $θ(τ_1,τ_2)$-continuous multifunction; lower quasi $θ(τ_1,τ_2)$-continuous multifunction